High photoluminescent carbon based dots with tunable emission color from orange to green. Issue 3 (5th January 2017) - Dong, Yongqiang; Chen, Yingmei; You, Xu; Lin, Wei; Lu, Chun-Hua; Yang, Huang-Hao; Chi, Yuwu
Abstract : A one-pot hydrothermal method was proposed for the synthesis of carbon based dots with high quantum yield and controllable long-wavelength photoluminescence. Abstract : A one-pot hydrothermal method was proposed for the synthesis of carbon based dots (CDs) with high quantum yield and controllable long-wavelength photoluminescence (PL). The PL mechanisms of the CDs were discussed, and a common model has been proposed. Furthermore, the obtained CDs showed excellent biocompatibility and high PLQYs (more than 20%), and presented great potential bio-applications.